PRENATAL DIAGNOSIS OF TAUSSIG BING ANOMALY WITH COARCTATION OF THE AORTA - CASE REPORT - Ana Pejkovska; Maja Pejkovska Ilieva; Mirjana Kjaeva Pejkovska; Pavle Dimchev; Igor Samardjiski (SHMSHM - AAMD, 2025)
Taussing Bing anomaly is a rare congenital heart malformation. Congenital heart defects (CHDs) represent a formidable global health challenge, frequently necessitating intricate surgical interventions, particularly in the vulnerable populations of neonates and infants. Among these, anomalies involving the great arteries and ventricular septal defects (VSDs) pose unique difficulties due to their complex anatomy and profound physiological impact on the developing cardiovascular system. We present a case of a fetal cardiac anomaly initially diagnosed as transposition of the great arteries (TGA) with subsequent identification of coarctation of the thoracic aorta (CoA). Post-termination autopsy confirmed Taussig Bing anomaly (TBA), a rare conotruncal malformation characterized by a double-outlet right ventricle (DORV) with subpulmonary ventricular septal defect (VSD) and malposition of the great arteries. This case highlights the diagnostic challenges in prenatal imaging and the importance of multidisciplinary evaluation in complex congenital heart disease (CHD).